The performance of corporate-bond mutual funds: Evidence based on security-level holdings - Gjergji Cici; Scott Gibson (University of Cologne, Centre for Financial Research (CFR), 2010)
This is the first study of corporate-bond mutual fund performance that examines detailed security-level holdings and returns. The new database allows us to decompose the costs and benefits of active management. In contrast to prior research on equity funds that shows evidence of stock-selection ability, we do not find evidence consistent with bond fund managers, on average, being able to select corporate bonds that outperform other bonds with similar characteristics. We find neutral to weakly positive evidence of ability to time corporate bond characteristics. Overall results show that the costs of active management on average appear larger than the benefits.
Keywords: 330; Rentenfonds; Industrieobligation; Portfolio-Management; Kapitalertrag; Kosten-Nutzen-Analyse; Schätzung; USA